2022
DOI: 10.3389/fpls.2022.971927
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis revealed differential gene expression involved in wheat leaf senescence between stay-green and non-stay-green cultivars

Abstract: Breeders agree that leaf senescence is a favorable process for wheat seed yield improvement due to the remobilization of leaf nutrients. However, several studies have suggested that staying green may be an important strategy for further increasing wheat yields. In this study, we performed a comparative transcriptome analysis between wheat cultivars CN17 and CN19 after heading and also measured photosynthetic parameters, chlorophyll (Chl) contents, and antioxidant enzyme activities at various time points after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
2
4
0
Order By: Relevance
“…H 2 O 2 and MDA levels were found to be lower in LS compared to SS during DIS, which could be explained by the increased activities of antioxidant enzymes (SOD and CAT) in LS (Figure 2). These results suggest that the activation of the enzymatic ROS scavenging system in LS reduced ROS accumulation and delayed its dark-induced leaf senescence, which was supported by previous studies in other plant species [26,36]. Flavonoids were previously reported to possess the capacity to scavenge ROS and mitigate oxidative damage in plants [37].…”
Section: Physiological Characteristics Of Foxtail Millet Exhibiting V...supporting
confidence: 84%
See 2 more Smart Citations
“…H 2 O 2 and MDA levels were found to be lower in LS compared to SS during DIS, which could be explained by the increased activities of antioxidant enzymes (SOD and CAT) in LS (Figure 2). These results suggest that the activation of the enzymatic ROS scavenging system in LS reduced ROS accumulation and delayed its dark-induced leaf senescence, which was supported by previous studies in other plant species [26,36]. Flavonoids were previously reported to possess the capacity to scavenge ROS and mitigate oxidative damage in plants [37].…”
Section: Physiological Characteristics Of Foxtail Millet Exhibiting V...supporting
confidence: 84%
“…It has been reported that the promoter of SAG39 is implicated in the negative regulation of leaf senescence in rice [48]. A comparative transcriptome analysis further revealed that TaSAG39 delayed the senescence process by maintaining the stability of chlorophyllprotein complexes in a stay-green wheat cultivar [26]. Our research also indicated that the senescence-delaying foxtail millet LS maintained a higher chlorophyll content during the DIS (Figure 1B).…”
Section: Candidate Sags That Regulate Dark-induced Leaf Senescence In...supporting
confidence: 71%
See 1 more Smart Citation
“…Previous studies on the genetics of SG traits in wheat have primarily focused on identifying QTL [ 8 , 10 , 49 ]. In this study, by combining genetic analysis, we observed that the SG candidate genes identified here had signs of selection in past wheat breeding.…”
Section: Discussionmentioning
confidence: 99%
“…According to Thomas and Ougham (2014), breeders tend to avoid using cosmetic stay-greens because they do not offer any yield benefits. The opposite type, functional stay-green, is more desirable for breeding purposes as photosynthesis is maintained longer during the maturation phase (Thomas & Ougham, 2014; Li et al ., 2022). However, screening populations for functional stray-green genotypes is complicated as it would require gas-exchange measurements at multiple time points on a large number of individuals, which is not feasible without a large number of instruments and trained users.…”
Section: Discussionmentioning
confidence: 99%